2001
DOI: 10.1097/00005768-200104000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different sports on bone density and muscle mass in highly trained athletes

Abstract: This cross-sectional study has shown that athletes, especially those engaged in high-impact sports, have significantly higher total BMD and AMM than controls. These results suggest that the type of sport activity may be an important factor in achieving a high peak bone mass and reducing osteoporosis risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
189
1
18

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(223 citation statements)
references
References 29 publications
15
189
1
18
Order By: Relevance
“…Among these studies, a few use the strength training, trying to increase the BMD in individuals submitted to that type of physical activity (7,13,14,17) . In general, the same studies have shown positive results related to the BMD (8,15,(17)(18)(19)(20)(21)(22)(23) . Nevertheless, despite this possible benefic effect, quite large training volumes may cause a damage on the BMD, and it seems that such damage is closely related to the disturbance in the hormonal homeostasis of the organism (5,6,24) .…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…Among these studies, a few use the strength training, trying to increase the BMD in individuals submitted to that type of physical activity (7,13,14,17) . In general, the same studies have shown positive results related to the BMD (8,15,(17)(18)(19)(20)(21)(22)(23) . Nevertheless, despite this possible benefic effect, quite large training volumes may cause a damage on the BMD, and it seems that such damage is closely related to the disturbance in the hormonal homeostasis of the organism (5,6,24) .…”
mentioning
confidence: 85%
“…In fact, the BMD seems to respond to a higher training intensity both in human (3) and in animal models (27) . Related to the bone remodeling, according to Andreoli et al (15) , in the strength induction, the deformation that occurs in the structures involved can lead to an optimum formation level and to an inhibition in the reabsorption that occurs within the normal remodeling cycle.…”
Section: Action Of the Exercising On The Bone Structure And Remodelingmentioning
confidence: 99%
See 1 more Smart Citation
“…The change of the parts of the extremities regarding the preparatory period is insignifi cant. Segmental and total bone mineral density were measured by Andreoli et al (2001) in judo, karate and water-polo athletes, and the study has shown that athletes engaged in high impact sports have signifi cantly higher total bone mass and bone mass density.…”
Section: Discussionmentioning
confidence: 99%
“…In this group the muscle mass of the lower extremities represents more than half of the total muscle mass, so sports promoting the development this muscles, such as running, soccer or cycling (Knechtle et al, 2007) may result advantageous and more efficient to prevent sarcopenia compared to other sports that involve a higher muscle mass development of the upper limbs or trunk, like swimming or rowing, for example (Andreoli et al, 2001).…”
Section: Discussionmentioning
confidence: 99%